The Influence of Job Stress and Work Culture on the Perfomance of Employees at Company, Bandung City - Peni Cahyati; Elvie Maria; Nandan Limakrisna; Nurdiana Mulyatini; April Gunawan M (Greenation Research & Yayasan Global Resarch National, 2024)
The objective of this research is to determine the impact of work-related stress on the performance of employees at The X Company firm. (2) This study examines the impact of work culture on employee performance at The X Company company. (3) Additionally, it investigates the role of job stress on work culture at The X Company company. (4) This study examines the impact of job stress and work culture on employee performance at The X Company enterprise. The research was conducted at the companyInvestama's facility, X Company. A study was done at Investama's firm, X Company, with a sample size of 30 individuals. The data utilized in this study consist of primary data and secondary data. Data collecting methods include techniques such as document recording, interviews, and surveys. For doing data analysis using route analysis. The findings of this study indicate that job stress and work culture have a favorable impact on employee performance at The X Company organization. (2) Work stress has a beneficial impact on the work culture at The X Company firm. (3) Work stress has a favorable impact on staff performance at The X Company firm. (4) The work culture of The X Company organization has a beneficial impact on staff performance.